PELATIHAN PENINGKATAN KOMPETENSI CALON GURU BERSAMA PRAKTISI PENDIDIKAN MELALUI STIMULASI PROYEK MANAGEMENT - Hersiyati Palayukan; Inelsi Palengka; Evy Lalan Langi; Septi Triyan; Nanda Saputra (STKIP PGRI SITUBONDO, 2023)
The challenge that is a community need is the availability of multi-competent and resilient teachers. In addition, teachers who are always ready to learn and hone their competencies following regulatory changes and developments in science and technology are needed. This is the basis for the need to provide training to prospective teachers before plunging into the community and serving in the world of education. The purpose of this service is to increase the competency of prospective teachers with the help of education practitioners who have had a lot of experience in dealing with everyday techniques in schools. The competencies that need to be formed are about how to manage schools and their scientific development. With the target participants being prospective teachers, there is great hope to hone their competence. The method of implementing online training with participants from 3 universities. This training service activity helps prospective teachers to improve their competence with school management projects. In addition, competence in the scientific field also increases insight and skills. Through joint practice with given problems on the assignment to increase the participants' skills and abilities.